Dry Port Location Selection: A Case Study of Tanjung Intan Port - Kurnia, Gita; Hanan Fatika Adzkia; Nur Layli Rachmawati (Journal of Emerging Supply Chain, Clean Energy, and Process Engineering, 2023)
A dry port is established as an inland extension of a port. Tanjung Intan Port, which is located in Cilacap and within the range of tsunami risk zones, has no dry port to accommodate its distant customers. This research proposes a dry port location selection for Tanjung Intan Port with the following main criteria: safer from tsunami risks and achieve maximal demand coverage. By applying AHP (Analytical Hierarchy Process), the location candidates were ranked and further selected using MCLP (Maximum Coverage Location Problem) to choose the best candidate. The study result selects Maos railway station as the most attractive dry port location. The feasibility study result shows that the location has: (1) a lower risk of tsunami impact, (2) potential for the port’s market expansion, (3) less pollution potential, (4) adequate railway tracks, (5) large area, (6) good location away from densely populated areas and, (7) easy access for trucks.